2021
DOI: 10.3389/fcvm.2021.577742
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Fluctuation and Mortality in Critically Ill Myocardial Infarction Patients: A Retrospective Cohort Study

Abstract: Background: Whether heart rate (HR) fluctuation after admission has an impact on the outcomes of critically ill myocardial infarction (MI) patients in intensive care unit remains unknown.Methods: A total of 2,031 MI patients were enrolled from the Medical Information Mart for Intensive Care (MIMIC-III) database. HR fluctuation was calculated as the maximum HR minus the minimum HR in the initial 24 h after admission. Participants were divided into 3 groups, namely, low HR fluctuation [<30 beats per minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…Also, the U-shaped curve was seen in critically ill patients, providing a new insight for optimizing HR control strategies. 20 Yet, other studies observed a J-shaped association in acute ischemic stroke patients, 21 myocardial infarction patients, 22 and even in the general population. 23 In agreement with the latter observations, we also observed a typical J-shaped curve for the association between RHR and 1-year mortality, and 70 bpm exhibited the lowest mortality risk.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Also, the U-shaped curve was seen in critically ill patients, providing a new insight for optimizing HR control strategies. 20 Yet, other studies observed a J-shaped association in acute ischemic stroke patients, 21 myocardial infarction patients, 22 and even in the general population. 23 In agreement with the latter observations, we also observed a typical J-shaped curve for the association between RHR and 1-year mortality, and 70 bpm exhibited the lowest mortality risk.…”
Section: Discussionmentioning
confidence: 96%
“…Also, the U-shaped curve was seen in critically ill patients, providing a new insight for optimizing HR control strategies. 20 Yet, other studies observed a J-shaped association in acute ischemic stroke patients, 21 myocardial infarction patients, 22…”
Section: Dovepressmentioning
confidence: 97%
“…MIMIC is the largest open source and free clinical database in the critical care and emergency department, based on BIDMC’s intensive care inpatient system. MIMIC-IV (version 1.0) is the latest version, which contains data from 2008 to 2019 ( Guo et al, 2021 ; Lu et al, 2021 ; Song et al, 2021 ). We completed the courses required to use the database and obtained the corresponding certificate.…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory tests included counting the number of or estimating the levels of white blood cells (WBC), hemoglobin, platelets, anion gap, sodium, potassium, chloride, bicarbonate, creatinine, blood urea nitrogen (BUN), prothrombin time, activated partial thromboplastin time, troponin T (cTnT), and lactate within the first 24 h after ICU admission. 17,18 Interventions involved the use of vasopressor medicine, dialysis, mechanical ventilation, and percutaneous coronary intervention (PCI). Except for cTnT and lactate, the missing values of the other variables were all within 10%, which were filled by multivariate multiple imputation with chained equations; by contrast, cTnT and lactate were regarded as dummy variables in the statistical analysis to reduce the possible bias of simple filling.…”
Section: Participants and Designmentioning
confidence: 99%